2021
DOI: 10.1101/2021.03.10.21253330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the COVID-19 illness experience to inform the study of post-acute sequelae and recovery: a qualitative study

Abstract: We aimed to characterize the variability in the illness experience and recovery process from COVID-19. We conducted 24 in-depth individual interviews with participants enrolled in the Long-term Immunological Impact of Novel Coronavirus (LIINC) cohort study in San Francisco, California from June through October of 2020. Participants were adults who had a previously confirmed positive SARV-CoV-2 nucleic acid amplification test result, had recovered or were recovering from acute infection, and underwent serial ev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Twenty-three studies reported the presence of worry in patients, for various reasons. Some people expressed concern about their illness, fearing that they would not receive timely medical assistance, and that the disease would worsen resulting into complications or even death [ 11 , 14 , 18 ] . Some people are afraid that they will infect their family and friends, and damage their health [ 9 , 12 , 13 , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-three studies reported the presence of worry in patients, for various reasons. Some people expressed concern about their illness, fearing that they would not receive timely medical assistance, and that the disease would worsen resulting into complications or even death [ 11 , 14 , 18 ] . Some people are afraid that they will infect their family and friends, and damage their health [ 9 , 12 , 13 , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ] .…”
Section: Resultsmentioning
confidence: 99%
“…In ten studies, patients reported feeling miserable, and that the illness was an awful experience [ 9 , [11] , [12] , [13] , [14] , 18 , 21 , 26 , 28 , 29 ] . Unlike ordinary pneumonia infections, COVID-19 is associated with an intense attack on bodily systems by a highly functioning immune system, in addition to compromised lung function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both qualitative and quantitative studies have explored the impact of ICU admission on COVID-19 survivors and their relatives in the first wave of the pandemic. 17,18 The recovery pathway from the perspectives of both stakeholders has been the focus of several studies. 9,12,[18][19][20][21] However, to our knowledge, no previous qualitative studies have explored the recovery needs of survivors and their families over time.…”
Section: Introductionmentioning
confidence: 99%